The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1159/000186384
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Precursor of Methylguanidine in Rats with Renal Failure

Abstract: Each of creatinine (Cr), guanidinoacetic acid (GAA) and arginine (Arg) was administered intraperitoneally to rats with renal failure, and the levels of methylguanidine (MG) in the serum, liver, kidney, muscle and urine were determined at certain intervals. The levels of MG in the serum, liver, kidney, muscle and urine after Cr administration increased markedly with time. The amount of total MG at 24 h was estimated to be 114 μg/100 g body weight, which accounted for 0.46% of the Cr dose. In contrast, changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…This increase is either due to reduced excretion or due to increased production. Indeed, it has been proposed that in patients with chronic renal failure, an increase in MG production may arise from the conversion of creatinine to MG (Orita et al, 1978;Yokozawa et al, 1990;Yokozawa et al, 1991). Furthermore, Natelson & Sherwin (1979) suggested that urea could be converted to creatine, via canavanine in a supposed 'guanidinic cycle', and subsequently converted in creatinine to be included in the formation of MG.…”
Section: Discussionmentioning
confidence: 99%
“…This increase is either due to reduced excretion or due to increased production. Indeed, it has been proposed that in patients with chronic renal failure, an increase in MG production may arise from the conversion of creatinine to MG (Orita et al, 1978;Yokozawa et al, 1990;Yokozawa et al, 1991). Furthermore, Natelson & Sherwin (1979) suggested that urea could be converted to creatine, via canavanine in a supposed 'guanidinic cycle', and subsequently converted in creatinine to be included in the formation of MG.…”
Section: Discussionmentioning
confidence: 99%
“…These tissues (kidney, heart or liver) injury or dysfunction caused by iron–ROS positively interaction underpins the early stage of related pathological symptom. ROS such as hydroxyl radicals and O 2 •− , as well as uremic toxins are mainly responsible for renal failure (Paller et al 1984; Wills 1985; Yokozawa et al 1991). In addition, free radicals play a considerable role in the synthesis of the uremic toxins Cr, MG and GSA (Fujitsuka et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas nearly 100 different guanidino compounds have been found in the natural world, those found in the serum and urine of patients with renal failure include guanidine, guanidinosuccinic acid, guanidinopropionic acid, guanidinoacetic acid, arginine, creatinine (Cr), creatine, and methylguanidine (MG). Among these compounds, MG has been studied from various aspects in relation to its toxicity [9, 10], quantification [11], precursor [12, 13, 14], organs where it is produced [15, 16, 17], production pathways [18, 19, 20, 21, 22], factors influencing its production [23, 24, 25], etc. However, few studies have examined the specific location of MG production in the kidney and the factors involved in its production.…”
Section: Introductionmentioning
confidence: 99%